Water Oxidation Catalysis by Synthetic Manganese Oxides with Different Structural Motifs: A Comparative Study. Issue 42 (1st September 2015) - Frey, Carolin E.; Kurz, Philipp
Abstract Manganese oxides are considered to be very promising materials for water oxidation catalysis (WOC), but the structural parameters influencing their catalytic activity have so far not been clearly identified. For this study, a dozen manganese oxides (MnOx) with various solid‐state structures were synthesised and carefully characterised by various physical and chemical methods. WOC by the different MnOx was then investigated with Ce4+ as chemical oxidant. Oxides with layered structures (birnessites) and those containing large tunnels (todorokites) clearly gave the best results with reaction rates exceeding 1250 <alternatives> <![CDATA[${{\rm{mmol}}_{{\rm{O}}_{\rm{2}} } }$]]> <inline-graphic xlink:href="ark:/27927/pgk2qr7g13" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> <alternatives> <![CDATA[${{\rm{mol}}_{{\rm{Mn}}}^{ - 1} }$]]> <inline-graphic xlink:href="ark:/27927/pgk2qr7g34" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> h−1 or about 50 μmolO2 m−2 h−1. In comparison, catalytic rates per mole of Mn of oxides characterised by well‐defined 3D networks were rather low (e.g., ca. 90 <alternatives> <![CDATA[${{\rm{mmol}}_{{\rm{O}}_{\rm{2}} } }$]]> <inline-graphic xlink:href="ark:/27927/pgk2qr7fqz" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> <alternatives> <![CDATA[${{\rm{mol}}_{{\rm{Mn}}}^{ - 1} }$]]> <inline-graphic xlink:href="ark:/27927/pgk2qr7frg" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> h−1 for bixbyite, Mn2O3), but impressive if normalised per unit surface area (>100 <alternatives> <![CDATA[${{\rm{{\rm \mu} mol}}_{{\rm{O}}_{\rm{2}} } }$]]> <inline-graphic xlink:href="ark:/27927/pgk2qr7fs0" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> m−2 h−1 for marokite, CaMn2O4). Thus, two groups of MnOx emerge from this screening as hot candidates for manganese‐based WOC materials: 1) amorphous oxides with tunnelled structures and the well‐established layered oxides; 2) crystalline MnIII oxides. However, synthetic methods to increase surface areas must be developed for the latter to obtain good catalysis rates per mole of Mn or per unit catalyst mass.